A systematic review of neurological symptoms and brain abnormalities in SARS-CoV-2 infections - Daniel Montoya; Jacobo Albert; Sarah Lopez-Martin (Academia Medicine)
The aim of this systematic review is to show some clear evidence of COVID-19 infections in the human brain and draw attention to the neurological symptoms that were described during the early stages of the pandemic. A systematic literature search, conducted using ScienceDirect, PubMed, and Google Scholar, returned articles published from January 1 to October 1, 2020. Five hundred and ninety five articles were retrieved and screened for specificity and brain data availability associated with SARS-CoV-2 in adults. After the selection criteria were applied, 87 articles remained, comprising 55 case reports and 32 cohort studies, which involved 711 men and 310 women. The majority of reports listed altered states of consciousness as a symptom appearing post-admission or during the scanning process. Other symptoms included headaches, anosmia and ageusia, facial droop, and paralysis, among others. Parallel to these neurological symptoms, white matter hyperintensities were the most frequent finding with MRI brain scanning, while hypodensities accounted for most of the lesions described with CT scanning. There was a significant occurrence of hemorrhages and microbleeds, with a prevalence of multifocal intracerebral bleeding patterns in all cerebrum and cerebellum lobes. The most affected brain area was the corpus callosum, followed by the lateral ventricles and surrounding areas, the midbrain, the basal ganglia, the internal capsule, the olfactory bulb, the thalamus, the insular cortex, and the amygdala. There are unknown long-term effects that may impact currently infected patients if the description of neurological symptoms and mapping of brain areas affected by SARS-CoV-2 are not accomplished.